Pengaruh Metode Pembelajaran Reka Cerita Gambar terhadap Kemampuan Berbicara Anak Usia 5-6 Tahun - Rahmah, Rahmah; Andresni, Hafiko (Generasi Emas : Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Speaking ability is a crucial aspect of early childhood language development that forms the foundation for cognitive, social, and emotional growth. Observations at TK Annur Izz Zalfa revealed that most children aged 5–6 years still have difficulties responding to questions, constructing simple sentences, and expressing ideas verbally due to passive and less communicative learning practices. This study aimed to determine the effect of the Picture Storytelling method on the speaking ability of children aged 5–6 years. Conducted in October 2025, this research employed a quantitative approach using a quasi-experimental design with a pretest–posttest non-equivalent control group. The sample consisted of 24 children selected through purposive sampling and divided into an experimental group (12 children) and a control group (12 children). Data were collected through pretests and posttests and analyzed using normality, homogeneity, paired t-test, and independent t-test analyses. The results showed a significant improvement in the experimental group, with the mean score increasing from 27.50 to 38.92 (p = 0.0001), while the control group showed a smaller increase from 28.53 to 30.33 (p = 0.0001). The independent t-test indicated a significant difference in effectiveness between the two groups (p = 0.039). In conclusion, the Picture Storytelling method is effective in improving the speaking ability of children aged 5–6 years and is recommended as an interactive language learning strategy.